L.fulica Mucins: The Novel Source for the Evaluation of Antibacterial Efficacy against Various Pathogenic Bacterial Species. - L, Aishwarya; S, Shabana Begum; Arshi, Sumaiya; Panneerselvam, Kiruthika (International Journal of Life Science and Pharma Research, 2025)
Lissachatina fulica, the giant African land snail, is one of the most invasive and widely imported land snail species globally. It has been introduced to numerous Asian nations, Pacific and Caribbean islands, and Brazil. L.fulica, secretes mucus to help in crawling and protection because it serves as a lubricant to shield sensitive epithelial body surfaces from various physical and mechanical harms. The mucin that L.fulica releases has attracted attention from all around the world due to its pharmacological similarities to other gastropods. Snail mucins have recently emerged as a treasure mine of new possibilities in the domains of biology, chemistry, biotechnology, and biomedicine. Particular applications for snail mucuses include wound healing, skin care products, surgical glues, and stomach ulcer treatment. Recent advances in integrated omics (genomic, transcriptomic, proteomic, and glycomic) technology have produced more novel biomaterials due to improved characterization of gastropod mucins. Today, antimicrobial resistance caused by microorganisms is one of the gravest medical issues impacting virtually all nations. Newer antimicrobial therapies that lessen this resistance need to be created right away. This research emphasizes on the antibacterial activity of mucin against various bacterial species such as Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae, Shigella dysenteriae, and Salmonella typhimurium. Therefore, the mucin was extracted by periodically spraying with an acid-stimulating solution i.e., 5% citric acid by diluting with distilled water. The stimulating fluid produced a large amount of mucus without stressing or harming the snail. The antibacterial activity of mucin was detected by using agar disc diffusion method which showed highest zone of Inhibition against Staphylococcus aureus with 25mm and agar well diffusion method showed highest zone of Inhibition against Shigella dysenteriae with 16mm amongst other various Bacterial species mentioned above. Using Bradford’s coomassie brilliant blue assay, the protein estimation of mucin was determined. The snail’s internal and external shell was examined in order to isolate the microorganism present there. This work is aimed at assessing the antibacterial activity of mucin against various pathogenic bacteria.